LEGAL RESPONSIBILITY OF THE HOLDING COMPANY TO SUBSIDIARIES IN THE LETTER OF APPOINTMENT AND DETERMINATION OR ATPM AT PT. THERMO TECH SOLUTIONS ACCORDING TO LAW NO. 20 OF YEAR 2016 ABOUT BRAND - Ahmad Feri Tanjung; Heriyanti Heriyanti; Angella Yang (International Journal of Latin Notary, 2021)
The rapid progress of the business world has its influence on businesses and companies. To spread its wings and develop its business formed an independent limited liability company but still in the same ownership and control that is still centralized commanded by a company commonly referred to as a holding company. In its activities, please be aware of the position of the holding company with subsidiaries as stated in the Statement and Appointment of ATPM regarding the use of the brand. Therefore, the issue raised in this thesis is how the holding company is responsible for the subsidiaries in the ATPM Statement and Appointment letter regarding the brand. This research uses the empirical legal research method or also called the observation method that is by processing and using field data as the main data source and library material related to the problem. Based on the results of the study, it is known that the responsibility of the holding company as a subsidiary in the letter of Appointment and Determination of ATPM regarding the brand is the holding company is fully responsible for the quality of products marketed by its subsidiaries, and the subsidiaries are fully responsible in case of brand misuse.